A matter of taste: direct detection of female mating status in the bedbug. - Siva-Jothy, Michael T (2003)
Males of the bedbug, Cimex lectularius, traumatically inseminate females by inserting a needle-like intromittent organ (penis) through the female's abdominal wall after she has fed. We demonstrate that: (i) mating duration determines ejaculate size; (ii) a female's first copulation in a bout of copulations always lasts longer than subsequent copulations; (iii) the intromittent organ bears sensillae; (iv) males use their intromittent organ to 'taste' whether their current mate has recently copulated; and (v) the consequence of detecting female mating status is the reduction of copulation duration and ejaculate size. We discuss why male bedbugs might show this pattern of ejaculate-size adjustment.